FAKTOR-FAKTOR YANG MEMPENGARUHI PETANI TERHADAP JUMLAH PEMBELIAN PUPUK CAIR - PURNOMO, DWI; JAMHARI, JAMHARI; IRHAM, IRHAM; DARWANTO, DWIDJONO HADI (Jurnal Social Economic of Agriculture, 2015)
Farmers behavior in the purchase of fertilizers is influenced by many factors are complex and heterogeneous. Farmers' behavior can be influenced by different social, cultural and agricultural environments. Such behavior may also different between types of fertilizer. This study aimed to analyze the factors that affect farmers on the purchase amount of liquid fertilizer in approach behavior theory. This research was conducted with survey approach through interviews with a list of questions (questionnaire) of the 100 respondents onion farmer in Brebes Central Java in April-May 2015. The results of this study found that the purchases amount of liquid fertilizer influenced by income, experience, land area, the productivity of onion, the growing season, recommendations of other farmers, agricultural extension information, field trials, and recommendations of store.